Impact of dietary chia seed supplementation on body weight, breast meat proximate composition, hematological and biochemical parameters, and gut health in broiler chickens - Popy Khatun; Sabbya Sachi; Rafiqul Islam; Kazi Rafiq; Purba Islam; Bapon Dey; Muhammad Tofazzal Hossain; Md. Zahorul Islam (Discover Applied Sciences)
Abstract The use of natural feed additives in poultry nutrition have been developed due to concerns over antibiotic resistance and consumer demand for healthier meat. Chia seeds (Salvia hispanica L.) are a nutrient-dense functional feed rich in fiber, protein, omega-3 fatty acids, and a range of micronutrients. However, their effects on broiler health and performance remain underexplored. This study assesses the impacts of chia seed on the body weight, nutritional composition, hemato-biochemical parameters and gut health in broiler chickens. Sixty hatched broilers were divided equally into five groups: commercial diet, hand-mixed diet, hand-mixed diet supplemented with 1%, 5%, and 10% chia seeds. The supplemented diet was provided from day 14 to 35. The 5% chia seed-supplemented group had the highest body weight and increased dry matter and protein content of breast meat. Chia seed supplementation at 5% and 10% concentrations increased red blood cells, hemoglobin, hematocrit and serum HDL (high-density lipoprotein) values while other hematological and serum biochemical parameters remained unchanged. Gut microbiota analysis showed no overall shift in viable bacterial count, but lactobacilli count was increased in the 5% chia seed group. The villi height, width and surface area were reduced, but crypt depth and mucosal thickness were increased. Our data indicated that 5% chia seed supplementation for two weeks enhances growth performances and gut health, while long-term consumption may have adverse effects. Further researches are required to optimize the dose and duration of chia seed supplementation in broiler diet.